2017
DOI: 10.18052/www.scipress.com/ilcpa.72.37
|View full text |Cite
|
Sign up to set email alerts
|

Photophysics of Caffeic, Ferulic and Sinapic Acids with α- and β-Cyclodextrins: Spectral and Molecular Modeling Studies

Abstract: Abstract. Encapsulation of caffeic acid (CAA), ferulic acid (FEA) and sinapic acid (SIA) molecules with α-CD and β-CD was studied by UV-visible, fluorescence, time-resolved fluorescence and molecular modelling techniques. This analysis reports the dual emission properties of the above hydroxycinnamic acids (HCAs) in the aqueous cyclodextrin (CD) solution. The shorter wavelength bands originated from the locally excited state and the longer wavelength bands due to the emission from an intramolecular charge tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Compared to the poses found for the harpagoside, none of the two carboxylic acids could establish wide hydrogen‐bond interactions with the hydroxyl groups at the wide rim of the β‐cyclodextrin toroid. It is important to highlight that previous studies also demonstrated that metabolites such as the chlorogenic, vanillic, and sinapinic acids were able to effectively fit and interact with the β‐cyclodextrin (Górnas et al ., ; Rajendiran et al ., ; Xiong et al ., ). It is likely that the great predominance of harpagoside into the mixture elicited a β‐cyclodextrin saturation, thus interfering with the recovery of other components associated with the use of β‐cyclodextrin.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the poses found for the harpagoside, none of the two carboxylic acids could establish wide hydrogen‐bond interactions with the hydroxyl groups at the wide rim of the β‐cyclodextrin toroid. It is important to highlight that previous studies also demonstrated that metabolites such as the chlorogenic, vanillic, and sinapinic acids were able to effectively fit and interact with the β‐cyclodextrin (Górnas et al ., ; Rajendiran et al ., ; Xiong et al ., ). It is likely that the great predominance of harpagoside into the mixture elicited a β‐cyclodextrin saturation, thus interfering with the recovery of other components associated with the use of β‐cyclodextrin.…”
Section: Resultsmentioning
confidence: 99%
“…CA αCD [30,[33][34][35][36][37][38] βCD [30,[33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] HPβCD [30,33,34,44,45,[50][51][52] SBEβCD [53] MβCD [30,45] Crysmeb ® [33,34] DIMEB [54] RAMEB [33,34] γCD [30,36,55,56] Polymeric βCD [57] CGA αCD [31,58] βCD [31,40,42,48,…”
Section: Type Of CD Referencesmentioning
confidence: 99%
“…FA αCD [33,34,38,[74][75][76][77][78] TRIMEA [54] βCD [28,33,34,38,43,46,49,74,77,79,80] AminoβCD [29,74] HPβCD [33,34,73,78,79,[81][82][83][84] SBEβCD [53] MβCD [78] Crysmeb ® [33,34] DIMEB [54] RAMEB [33,34] γCD [74,77,85] HPγCD [78,84] Polymeric βCD [32] RA αCD [86] βCD [86][87][88][89] HEβCD [86] MβCD [86] Crysmeb ® …”
Section: Hca Type Of CD Referencesmentioning
confidence: 99%